Forestry Sector Corruption and Oligarchy: A Case Study of the Laman Kinipan Indigenous People, Central Kalimantan - Satria Unggul Wicaksana Prakasa; Achmad Hariri; Samsul Arifin; Asis Asis (Universitas Negeri Semarang, 2022)
Corruption is a serious problem in the rule of law development and sustainable development efforts. Law enforcement for weak environmental destroyers. On the other hand, the corruption process that is conducted involves a very strong power network and has impunity. This paper used a socio-legal based legal research method. Corruption in the forestry sector in Indonesia not only harms the state financially, but also creates environmental degradation that has an impact on human rights violations for the Laman Kinipan indigenous people. The Laman Kinipan indigenous people as victims of environmental damage have the right to get a solution from the perspective of being victims of environmental damage, both in the context of criminology, access to responsibility and accountability for environmental damage, then the impact of community sociology recovery, ensuring for perpetrators of environmental damage receive appropriate sanctions, as well as recovery in a collective sense. An effective anti-corruption mechanism with programs and compliance intended for business people and the government in preventing bribery corruption in the licensing sector, especially for PT.SML and the concession management circle at Laman Kinipan. Strengthening the concept of strict liability is a very strategic option in this era of industrialization to prevent environmental damage from corruption in the forestry sector.